2006
DOI: 10.1152/japplphysiol.00822.2005
|View full text |Cite
|
Sign up to set email alerts
|

Precooling leg muscle improves intermittent sprint exercise performance in hot, humid conditions

Abstract: We used three techniques of precooling to test the hypothesis that heat strain would be alleviated, muscle temperature (Tmu) would be reduced, and as a result there would be delayed decrements in peak power output (PPO) during exercise in hot, humid conditions. Twelve male team-sport players completed four cycling intermittent sprint protocols (CISP). Each CISP consisted of twenty 2-min periods, each including 10 s of passive rest, 5 s of maximal sprint against a resistance of 7.5% body mass, and 105 s of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
158
4
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(176 citation statements)
references
References 53 publications
(57 reference statements)
12
158
4
2
Order By: Relevance
“…Most researchers have addressed the effects of local cold treatments, where particular parts of the body were cooled or whole body was immersed in cold water on the level of chosen motor abilities or physical work capacity, under different temperatures [30][31][32][33][34][35][36]. Others evaluated the influence of cooling on the rate of recovery following injuries [19,22,27].…”
Section: Discussionmentioning
confidence: 99%
“…Most researchers have addressed the effects of local cold treatments, where particular parts of the body were cooled or whole body was immersed in cold water on the level of chosen motor abilities or physical work capacity, under different temperatures [30][31][32][33][34][35][36]. Others evaluated the influence of cooling on the rate of recovery following injuries [19,22,27].…”
Section: Discussionmentioning
confidence: 99%
“…Other research showed a positive influence of different cooling procedures, applied 20 min before the onset of sprint effort performed on an ergocycle, on the level of maximal anaerobic power [18]. Cooling the whole body prior to exercise causes a lowering of internal tempera ture, which positively influences thermoregulatory pro cesses during physical efforts of maximal intensity [35].…”
Section: Discussionmentioning
confidence: 99%
“…A short warmup prior to exercise may effectively diminish the negative effects of whole body cooling by elevating deep muscle temperature, thus confirming the thesis presented ear lier that incorporating a warmup procedure after whole accessible literature. Most scientists have addressed the effects of local cryotherapy treatments, where particu lar parts of the body were cooled, on the level of chosen motor abilities or physical work capacity, under different temperatures [18,[28][29][30][31][32][33]. Other authors evaluated the in fluence of local cooling on the rate of recovery following injuries [20,22,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local cooling interventions can be carried out using ice packs or immersion in cold water (Van Lunen et al, 2003;Verducci, 2000). When ice packs are applied over the muscle belly it leads to the reduction of skin and muscle temperatures resulting in changes in the Unauthenticated Download Date | 5/10/18 2:36 AM physiological proprieties of the muscle (Castle et al 2006;Petrofsky & Laymon, 2005;Rutkove, 2001). It has been shown that local muscle cooling may influence muscle resistance (Castle et al, 2006;Verducci, 2000) and force production (Oksa 2002;Oksa et al, 1997;Holewijn & Heus, 1992).…”
Section: Introductionmentioning
confidence: 99%